Effect of Hypoproteic and High-Fat Diets on Hippocampal Blood-Brain Barrier Permeability and Oxidative Stress - de Aquino, Cristhyane Costa; Leitão, Ricardo A.; Oliveira Alves, Luís A.; Coelho-Santos, Vanessa; Guerrant, Richard L.; Ribeiro, Carlos F.; Malva, João O.; Silva, Ana P.; Oriá, Reinaldo B. (Frontiers in Nutrition, 2019)
Worldwide, millions of people are exposed to dietary unbalance that impact in health and quality of life. In developing countries, like in Brazil, in poor settings, dietary habits, traditionally hypoproteic, are changing rapidly to western-type high-fat foods. These rapidly changing dietary habits are imposing new challenges to human health and there are many questions in the field that remain to be answered. Accordingly, we currently do not know if chronic consumption of hypoproteic (regional basic diet, RBD) or high-fat diets (HFD) may impact the brain physiology, contributing to blood-brain barrier (BBB) dysfunction and neuroinflammatory events. To address this issue, mice were challenged by breastfeeding from dams receiving standard, RBD or HFD from suckling day 10 until weaning. Immediately after weaning, mice continued under the same diets until post-natal day 52. Herein, we show that both RBD and HFD cause not only a peripheral but also a consistent central neuroinflammatory response, characterized by an increased production of ROS and pro-inflammatory cytokines. Additionally, BBB hyperpermeability, accounted by an increase in hippocampal albumin content, a decrease in claudin-5 protein levels and collagen IV immunostaining, was also observed together with an upregulation of vascular cell adhesion molecule 1 (VCAM-1). Interestingly, we also identified a significant astrogliosis, manifested by upregulation of GFAP and S100β levels and an intensification of arbor complexity of these glial cells. In sum, our data show that dietary unbalance, related with hypoproteic or high-fat content, impairs BBB properties potentially favoring the transmigration of peripheral immune cells and induces both a peripheral and central neuroinflammatory status. Noteworthy, neuroinflammatory events in the hippocampus may cause neuronal malfunction leading to cognitive deficits and long-term persistence of this phenomenon may contribute to age-related neurodegenerative diseases.